2018
DOI: 10.1371/journal.pone.0190952
|View full text |Cite
|
Sign up to set email alerts
|

Association of day 4 cumulative fluid balance with mortality in critically ill patients with influenza: A multicenter retrospective cohort study in Taiwan

Abstract: BackgroundFluid balance is a fundamental management of patients with sepsis, and this study aimed to investigate the impact of cumulative fluid balance on critically ill patients with influenza admitted to an intensive care unit (ICU).MethodsThis multicenter retrospective cohort study was conducted by the Taiwan Severe Influenza Research Consortium (TSIRC) which includes eight medical centers. Patients with virology-proven influenza infection admitted to ICUs between October 2015 and March 2016 were included f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…Currently, influenza infection remains a global health threat that is estimated to affect nearly five million people worldwide, resulting in 250 000 to 500 000 deaths in 2015 14. Our previous studies, investigating 336 patients with severe influenza requiring ICU management, showed the impact of an influenza epidemic on the healthcare system due to an abrupt increase in patients with severe influenza and found that lung-protective ventilation as well as fluid balance were early predictors for 30-day mortality in patients with severe influenza 15 16. These findings highlight the crucial need to develop an influenza-specific mortality prediction model for both the management of patients and the allocation of ICU resources during an influenza epidemic.…”
Section: Introductionmentioning
confidence: 90%
“…Currently, influenza infection remains a global health threat that is estimated to affect nearly five million people worldwide, resulting in 250 000 to 500 000 deaths in 2015 14. Our previous studies, investigating 336 patients with severe influenza requiring ICU management, showed the impact of an influenza epidemic on the healthcare system due to an abrupt increase in patients with severe influenza and found that lung-protective ventilation as well as fluid balance were early predictors for 30-day mortality in patients with severe influenza 15 16. These findings highlight the crucial need to develop an influenza-specific mortality prediction model for both the management of patients and the allocation of ICU resources during an influenza epidemic.…”
Section: Introductionmentioning
confidence: 90%
“…Accumulating evidence have shown the crucial need of the conservative fluid strategy in critically ill patients, 27 and we identified in other work the critical role of cumulative fluid balance in critically ill influenza subjects. 28 Therefore, the findings of this study suggest that a positive cumulative fluid balance may be a real-time indicator for VAE prevention by providing a warning that a patient is on track to develop a VAE secondary to pulmonary edema.…”
Section: Discussionmentioning
confidence: 80%
“…Using this definition, the study population was divided into 85 patients received early corticosteroid treatment and 156 patients without early corticosteroid treatment ( Table 1). The patients received early corticosteroid treatment had higher hospital mortality rate than those without early corticosteroid treatment [43.5% (37/85) vs. 19.2% (30/156), p < 0.001]. The patients receiving early corticosteroid treatment also had lower probability of survival than those without early corticosteroid treatment (log rank p < 0.001) ( Fig.…”
Section: Analyses Of the Whole Study Populationmentioning
confidence: 91%
“…This multicenter retrospective cohort study was conducted in the ICUs in eight medical centers across Taiwan during the 2015-2016 influenza epidemic [17][18][19]. The study was approved by the Institutional Review Board in each participating hospital.…”
Section: Study Cohortmentioning
confidence: 99%